Meningkatkan Efektivitas Pengelolaan SDM melalui Pendekatan Akuntansi di Perguruan Tinggi - Muslimin, Ulyana; Hasan, Hamida; Putri, Naulya Dwi; Haslindah, Haslindah; Jayanti, Iin Dwi (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to analyze the management of human resources (HR) in universities with an accounting approach. The results of the study show that human resource management using an accounting approach can increase effectiveness and efficiency in managing human resources. Although there are several challenges, the use of an accounting approach can help universities in improving employee performance and productivity. This study recommends the implementation of an accounting approach for human resource management to achieve better academic goals